(untitled) (Bangladesh Journal of Botany, 2018)
To determine the succession after a fire that occured in 1997 in the vicinity of Cekem and Halfeti villages, near Sanliurfa, Turkey work was carried out. The floristic changes in the area were observed during first six years and in the tenth year after the fire. The dominant species of burnt vegetation had a tendency to return towards a state similiar to the existined before fire. Most of the species prior to fire (98.7%) reappeared within the first six years and the vegetation nearly reached the prefire physiognomy. At the end of ten years, no significant differences in term of floristic composition and physiognomy were observed.